Different synaptic stimulation patterns influence the local androgenic and estrogenic neurosteroid availability triggering hippocampal synaptic plasticity in the male rat. (2nd February 2017) - Di Mauro, Michela; Tozzi, Alessandro; Calabresi, Paolo; Pettorossi, Vito Enrico; Grassi, Silvarosa
Abstract: Electrophysiological recordings were used to investigate the role of the local synthesis of 17β‐estradiol (E2) and 5α‐dihydrotestosterone (DHT) on synaptic long‐term effects induced in the hippocampal CA1 region of male rat slices. Long‐term depression (LTD) and long‐term potentiation (LTP), induced by different stimulation patterns, were examined under the block of the DHT synthesis by finasteride (FIN), and the E2 synthesis by letrozole (LET). We used low frequency stimulation (LFS) for LTD, high frequency stimulation (HFS) for LTP, and intermediate patterns differing in duration or frequency. We found that FIN reverted the LFS‐LTD into LTP and enhanced LTP induced by intermediate and HFSs. These effects were abolished by exogenous DHT at concentration higher than the basal one, suggesting a stimulus dependent increase in DHT availability. No effect on the synaptic responses was observed giving DHT alone. Moreover, we found that the inhibition of E2 synthesis influenced the HFS‐LTP by reducing its amplitude, and the exogenous E2 either enhanced HFS‐LTP or reverted the LFS‐LTD into LTP. The equivalence of the E2 concentration for rescuing the full HFS‐LTP under LET and reverting the LFS‐LTD into LTP suggests an enhancement of the endogenous E2 availability that is specifically driven by the HFS. No effect of FIN or LET was observed on the responses to stimuli that did not induce either LTD or LTP. This study provides evidence that the E2 and DHT availability combined with specific stimulation patterns is determinant for the sign and amplitude of the long‐term effects. Abstract : Local synthesizes of E2 and DHT is determinant for the long‐term effects observed in CA1 hippocampus. Finasteride, a blocking agent of DHT synthesis from testosterone (T), prevents the enhancement of the local DHT availability and induces a small LTP instead of LTD in response to LFS. Moreover, letrozole, a blocking agent of E2 synthesis from T, prevents the increase in local E2 availability and remarkably reduces the amplitude of LTP following HFS.